2002
DOI: 10.1098/rspb.2001.1817
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic–pallidal interactions are critical in determining normal and abnormal functioning of the basal ganglia

Abstract: The subthalamic nucleus (STN) and external globus pallidus (GP) form a recurrent excitatory-inhibitory interaction within the basal ganglia. Through a computational model of these interactions we show that, under the influence of appropriate external input, the two nuclei can be switched between states of high and low activity or can generate oscillations consisting of bursts of high-frequency activity repeated at a low rate. It is further demonstrated from the model that the generation of the repetitive burst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 33 publications
9
93
0
Order By: Relevance
“…Low-frequency oscillations observed in organotypic cultures of this circuit (Plenz and Kitai, 1999) have been captured by these models (Humphries and Gurney, 2001;Gillies et al, 2002;Terman et al, 2002) and are consistent with the residual oscillations seen in the in vivo recordings of Magill et al (2001). The combined results of the current and previous modeling studies thus provide considerable support for the proposal that the isolated STN-GP loop forms a low-frequency pacemaker circuit (Plenz and Kitai, 1999;Bevan et al, 2002).…”
Section: Relationship To Other Bg Modelssupporting
confidence: 68%
“…Low-frequency oscillations observed in organotypic cultures of this circuit (Plenz and Kitai, 1999) have been captured by these models (Humphries and Gurney, 2001;Gillies et al, 2002;Terman et al, 2002) and are consistent with the residual oscillations seen in the in vivo recordings of Magill et al (2001). The combined results of the current and previous modeling studies thus provide considerable support for the proposal that the isolated STN-GP loop forms a low-frequency pacemaker circuit (Plenz and Kitai, 1999;Bevan et al, 2002).…”
Section: Relationship To Other Bg Modelssupporting
confidence: 68%
“…Such connections are not present in our model, because we judged that the evidence for such connections (Hammond and Yelnik, 1983;Sato et al, 2000b) was not strong enough to consider that they play a prominent role in information transmission in the basal ganglia. We think that the reason why Gillies et al (2002) did not find oscillations without these connections is that they did not consider transmission delays between STN and GPe, and our results (Eq. 9) imply that these delays must exist for the oscillations to be present.…”
Section: Discussionmentioning
confidence: 52%
“…Relationship to other models There have been a number of other modeling studies that investigated the oscillations present in the basal ganglia (Gillies et al, 2002;Terman et al, 2002;Humphries et al, 2006;Leblois et al, 2006). Two of those studies (Gillies et al, 2002;) also focused on the STN-GPe circuit and found that it can generate oscillatory activity, but the mechanisms that generated these oscillations were very different from our model, as we now describe.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations